Deletion of Asrgl1 Leads to Photoreceptor Degeneration in Mice - Zhou, Yu; Tian, Wanli; Jiang, Xiaoyan; Yang, Huining; Jiang, Zhilin; Li, Xiao; Jiang, Dan; Sun, Kuanxiang; Yang, Yeming; Liu, Wenjing; Zhu, Xianjun (Frontiers in Cell and Developmental Biology, 2022)
The asparaginase and isoaspartyl peptidase 1 (ASRGL1) is a L-asparaginase and beta-aspartyl peptidase enzyme that may be involved in the formation of L-aspartate, a neurotransmitter that can operate as an excitatory neurotransmitter in some brain regions. Although variants in ASRGL1 have been reported in retinitis pigmentosa (RP) patients, the in vivo functions and mechanisms of ASRGL in RP remain unknown due to the lack of suitable disease models. To explore the role of ASRGL in RP, we generated a Asrgl1 knockout mouse model (Asrgl1 KO) using the CRISPR/Cas9 technique. Asrgl1 ablation in mice led to an attenuated electroretinogram (ERG) response around 8-month-old. The thickness of the outer nuclei layer (ONL) started to decrease around 9-month-old in Asrgl1 KO mice, and gradually intensified at 12- and 15-month-old. Immunostaining revealed thinner inner segment (IS) and thinner outer segment (OS) as well as the progressive degeneration of rod and cone cells in Asrgl1 KO mice. 149 transcriptional differential expressed genes (DEGs) were found by RNA-seq in Asrgl1 KO retina. These DEGs were linked to a number of biological processes that were considerably enriched, including gastrointestinal disease, organismal injury and abnormalities. By analysis of canonical pathway, glucocorticoid receptor signaling was the top significant canonical pathway altered in Asrgl1 KO retina. Several molecules, including NFE2L2, IL-4, Foxp3, and Fos, were in the central nodes of the interaction network in Asrgl1 KO retina. In summary, our study provided a knockout mouse model for a better understanding of the molecular mechanism for ASRGL1-related RP.